CME flux rope and shock identifications and locations: Comparison of white light data, Graduated Cylindrical Shell model, and MHD simulations. Issue 3 (25th March 2016) - Schmidt, J. M.; Cairns, Iver H.; Xie, Hong; St. Cyr, O. C.; Gopalswamy, N.
Abstract: Coronal mass ejections (CMEs) are major transient phenomena in the solar corona that are observed with ground‐based and spacecraft‐based coronagraphs in white light or with in situ measurements by spacecraft. CMEs transport mass and momentum and often drive shocks. In order to derive the CME and shock trajectories with high precision, we apply the graduated cylindrical shell (GCS) model to fit a flux rope to the CME directed toward STEREO A after about 19:00 UT on 29 November 2013 and check the quality of the heliocentric distance‐time evaluations by carrying out a three‐dimensional magnetohydrodynamic (MHD) simulation of the same CME with the Block Adaptive Tree Solar‐Wind Roe Upwind Scheme (BATS‐R‐US) code. Heliocentric distances of the CME and shock leading edges are determined from the simulated white light images and magnetic field strength data. We find very good agreement between the predicted and observed heliocentric distances, showing that the GCS model and the BATS‐R‐US simulation approach work very well and are consistent. In order to assess the validity of CME and shock identification criteria in coronagraph images, we also compute synthetic white light images of the CME and shock. We find that the outer edge of a cloud‐like illuminated area in the observed and predicted images in fact coincides with the leading edge of the CME flux rope and that the outer edge of a faint illuminated band in front of the CME leading edge coincides with the CME‐driven shock front. Key Points: Good agreement between observed and predicted heliocentric distances for CMEs and shocks A cloud‐like area in observations and predictions is the leading edge of the CME flux rope A band in front of the CME in observations and predictions is the CME‐driven shock front